Cursing, Crisis and Customary Knowledge in Early Modern English Townships - O'Brien, Karen. author. aut Link
VII, 278 p. 1 illus.
Keywords: This book provides a historical and socio-legal investigation into the prevalence of litigation arising from cursing and interpersonal hostility in the under-explored region of Northwest England during a period of acute socio-economic crisis in the seventeenth century. Contributing to the scholarship of magic and witchcraft, it shows the complex circumstances of the world of healing and harming using customary knowledge such as magic and folk medicine as it is variously presented in the documents of the legal system. While primary sources such as pamphlets have usefully informed numerous witchcraft studies, this book establishes popular belief derived from the depositions, interrogatories and various other manuscripts of the manorial, ecclesiastical and secular courts positioned within a micro historical early modern context. Karen O’Brien is Honorary Senior Lecturer at the University of Sydney, Australia. She is a social historian of comparative socio-legal history and criminology. Within a range of global, thematic and temporal contexts, and in an appraisal of the requests of the weak to the powerful, her publications investigate legal sources such as petitions and depositions to ascertain how people transcend the hardships of daily life, principally by appealing to the law for justice. Her research is internationally influential in the field of petitioning and her forthcoming research and publications address the wide-ranging area of customary knowledge in international comparative historical context.